Sertraline Hepatotoxicity: Report of a Case and Review of the Literature - GÜNDÜZ, FEYZA (SPRINGER, 2009)
Sertraline is a commonly prescribed selective serotonin reuptake inhibitor drug. Hepatotoxicity caused by sertraline is rare. Asymptomatic elevations in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels have been rarely reported and shortly normalize after discontinuation of the agent. We present a case of severe drug-induced hepatitis in a patient receiving sertraline. To our knowledge, this is the seventh case in the medical literature as being associated with severe hepatotoxicity. Since it is extremely rare, we do not suggest a strict laboratory monitoring. However, sertraline should be discontinued in cases with symptoms implying hepatotoxicity and the patients should be informed of the potential of this side effect.
Keywords: Sertraline; Hepatotoxicity; Transaminase